2021
DOI: 10.1002/cam4.3857
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of cervical cancer after a negative cytological diagnosis in Polish cervical cancer screening programme

Abstract: Risk factors of cervical cancer (CC) development are well investigated, however, those influencing the risk of a potential false negative cytology preceding diagnosis of an invasive CC are not. We have aimed to explore these factors according to the data from Organised Cervical Cancer Screening Programme (OCCSP) in Poland. A total of 2.36 million of Pap tests sampled in 2010–2012 within OCCSP were merged with the Polish National Cancer Registry to identify CC cases after abnormal cytology and after normal cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 45 publications
2
11
0
Order By: Relevance
“…Adenocarcinoma (ADC), a histological subtype of CC, was identified significantly more frequently than squamous cell carcinoma (SCC) among women with FN cytological results, compared to those with screen-detected cancer, due to their common location in the endocervical canal and more difficult sampling [ 57 , 59 , 60 , 61 ]. Based on the audit of over four thousand CC cases diagnosed in Sweden in 2002–2011, Wang et al concluded that women with normal screening results had an 89% lower risk of SCC and only 60% lower risk of ADC diagnosis [ 62 ].…”
Section: CC Screening and Triage Tests And Methods Their Performance ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Adenocarcinoma (ADC), a histological subtype of CC, was identified significantly more frequently than squamous cell carcinoma (SCC) among women with FN cytological results, compared to those with screen-detected cancer, due to their common location in the endocervical canal and more difficult sampling [ 57 , 59 , 60 , 61 ]. Based on the audit of over four thousand CC cases diagnosed in Sweden in 2002–2011, Wang et al concluded that women with normal screening results had an 89% lower risk of SCC and only 60% lower risk of ADC diagnosis [ 62 ].…”
Section: CC Screening and Triage Tests And Methods Their Performance ...mentioning
confidence: 99%
“…Based on the audit of over four thousand CC cases diagnosed in Sweden in 2002–2011, Wang et al concluded that women with normal screening results had an 89% lower risk of SCC and only 60% lower risk of ADC diagnosis [ 62 ]. The risk of obtaining a FN result, compared to a true positive cytology report, was shown to be over three times higher in women subsequently diagnosed with ADC, compared to SCC, and almost two times higher in those with diagnosis of carcinoma other than squamous and glandular type [ 61 ]. It also coincides with the trend of the raising rate of ADCs detection in countries with CC screening implemented; since this type of carcinoma is more difficult to diagnose in screening, the treatment of precancerous lesions is suspended, and they may develop to the fully invasive form of disease [ 63 ].…”
Section: CC Screening and Triage Tests And Methods Their Performance ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Individual countries around the world have used the methods listed above (CC screening, HPV vaccination) to create national prevention programs. In Poland, an organized screening program for CC was established in 2006, which involves performing Pap smearbased cervical cytology on women aged 25-59 years at 3-year intervals [17]. In December 2021, The Polish Society of Gynecologist and Obstetricians published recommendations including liquid-based cytology (LBC) in the regimen for cervical cancer (CC) screening.…”
Section: Introductionmentioning
confidence: 99%
“…The principles of CC prevention in public health care in Poland are presented in Table 1 [5,17,18,22,24], and information regarding the private health care based on the example of the provider included in our study are presented in Table 2 [32].…”
mentioning
confidence: 99%